IMPACT OF FOREIGN MARKET AND CURRENCY EXCHANGE RATE ON INDIAN IT STOCKS - Sharma, Rakesh Kumar (Digital Repository of Theses, 2023)
The stock market plays a crucial role in the economy of every nation. With globalization, the world's economies have become interlinked through trade, foreign investment, capital flow, and technological advancements. Many studies have examined the influence of foreign stock exchanges, currency exchange rates, and economic articles on the Indian stock market using only the Granger causality method without the use of different approaches such as machine learning. Hence, this study takes a more robust approach by incorporating ensemble methods of machine-learning, deep-learning-based, and statistical methods and using majority voting to examine the impact of foreign IT stock markets, currency exchange rates, and economic articles on the Indian IT stock market. The results indicate that foreign IT stock markets such as France, the United States of America, Britain, and Germany have a positive impact on the Indian IT stock market. As such, an increase in the USD_INR, JPY_INR, and SGD_INR currency exchange rates increases in the Indian IT stock market, whereas an increase in the MUR_INR rate corresponds with a decrease. Positive sentiments reflected in articles from The Hindu and The Financial Times correspond with an increase in the Indian IT stock market, while other representations of economic articles correspond with a decrease. The study's findings could be valuable for financial markets as they might fill the gap in understanding strategies to increase their IT stock indices and provide an-in-depth insights into developing different trajectories in the stock market. Moreover, the study will also assist portfolio managers and investment management organizations in developing more profitable investment strategies.